Cardiovascular changes in patients presenting with vertigo - Rosario, David D. M.; Sequeira, Anitha (International Journal of Research in Medical Sciences, 2018)
Background: The term dizziness often used to refer to a host of complaints which present in a similar manner. Of these vertigo is the most common. A thorough knowledge of cardiovascular changes that occur in subjects presenting with peripheral vertigo will help the treating medical practioner to promptly identify the cause of symptoms and prevent any confusion that may alter the course of treatment. The aim of this study to identify the changes in cardiovascular parameters that occur in patients with vertigo. Methods: Study was conducted at a tertiary care hospital during a period of two years during which 100 subjects where studied. Of these 50 where healthy adults which was taken as control group. Remaining 50 subjects where those who were admitted to hospital with a diagnosis of peripheral vertigo and termed as case group. Cardiovascular parameters where accessed in terms of pulse rate, rhythm, blood pressure and ECG Recordings among both the groups taken in static position and with 30 degree head tilt backwards and 45 degree angulation on either sides as is done during Dix-Hallpike’s maneuver immediately, after 3 minutes and 10 minutes of positioning the patient. Results: The study showed that there is no significant change in cardiovascular parameters in patients with vertigo when compared with healthy individuals in static position. Immediately following change in position of head there is sudden fall in pulse as well as blood pressure which then gradually comes back to baseline levels in healthy individuals. When there is a labyrinthine dysfunction in those who have hyper active labyrinth the pulse rate and Blood pressure increases sharply immediately after change in position then gradually comes back to baseline level. In hypo active labyrinth the pulse rate and blood pressure falls marginally compared to normal individuals and in dead labyrinths there is a significant fall in pulse rate and blood pressure immediately following change in position which then gradually reverts back to normal. Conclusions: From our study it is quite clear that there are considerable changes in cardiac parameters in patients presenting vertigo which should be kept in mind while evaluating the patients to prevent misdiagnosis. The study also proves a close coordination between vestibular system and central cardiovascular regulatory mechanisms during positional changes to maintain hemodynamic stability.